Digital Awareness Among Secondary School Teachers - Lect.Nasir Dakhel Sultan (Journal of College of Education, 2026)
The purpose of this research is to explore the level of digital awareness among secondary school teachers. To achieve this objective, the researcher employed the descriptive method. A core sample of 150 teachers was selected from the broader research population, which includes 1,543 secondary school teachers in Wasit Governorate. Based on the theoretical background of the study and relevant educational and psychological literature, the researcher developed a Digital Awareness Scale comprising four dimensions: digital security, digital education, privacy and data protection, and digital social communication. Each dimension was represented by 9 items, resulting in a total of 36 items in the scale. The psychometric properties of the scale were determined, including validity (both face and construct validity) and reliability, assessed through internal consistency using Cronbach’s Alpha formula. The study’s findings indicated that teachers possess a considerable level of digital awareness.